IDENTIFIKASI TELUR SOIL TRANSMITTED HELMINTHS (STH) PADA FESES ANAK-ANAK DENGAN METODE DIRECT SLIDE DAN PENGENDAPAN FORMALIN 10% - Yeli Hartuti (Akademi Kesehatan John Paul II Pekanbaru, 2022)
Worm infection is one of the diseases that is still a health problem in children in developing countries, especially in children who have not been able to maintain personal hygiene.Worm infections can be caused by soil-transmitted worms that have been contaminated by the eggs or larvae of the Soil Transmitted Helminth worm. Identification is done by 2 methods, namely Direct slide method and 10% formalin deposition. This research is a type of non-experimental research with cross sectional design and sampling technique using purposive sampling. The sample used is the feces of children aged 5-11 years. The results of the study were 17 samples of feces that were examined, it was found that there were 6 samples infected with STH (Positive) while the other 11 samples were not infected with STH (Negative). Frequency Distribution of Mother's Knowledge about Worm Infections, good knowledge of 11.76%, 29.41% sufficient and 58.82% less.